2016
DOI: 10.3171/2015.4.jns142760
|View full text |Cite
|
Sign up to set email alerts
|

Sequential changes in Rotterdam CT scores related to outcomes for patients with traumatic brain injury who undergo decompressive craniectomy

Abstract: OBJECT Rotterdam CT scoring is a CT classification system for grouping patients with traumatic brain injury (TBI) based on multiple CT characteristics. This retrospective study aimed to determine the relationship between initial or preoperative Rotterdam CT scores and TBI prognosis after decompressive craniectomy (DC). METHODS The authors retrospectively reviewed the medical records of all consecutive patients who underwent DC for nonpenetrating TBI in 2 hospitals from January 2006 through December 2013. Univa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
21
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(25 citation statements)
references
References 30 publications
3
21
0
1
Order By: Relevance
“…28 The authors concluded that the Rotterdam CT scoring system can be a relatively objective, simple, and practical tool to prognosticate the outcome in both adults and pediatric patients with TBI. 2,28,30,31 In our study, we found that easy-to-use model and result showed that the higher the Rotterdam CT score, the poorer the outcome (it is in agreement with published literature). 2,28,30,31…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…28 The authors concluded that the Rotterdam CT scoring system can be a relatively objective, simple, and practical tool to prognosticate the outcome in both adults and pediatric patients with TBI. 2,28,30,31 In our study, we found that easy-to-use model and result showed that the higher the Rotterdam CT score, the poorer the outcome (it is in agreement with published literature). 2,28,30,31…”
Section: Discussionsupporting
confidence: 91%
“…29 In the Rotterdam CT score, the authors included individual CT characteristics (i.e., the status of basal cisterns, midline shift, and types of mass lesions or intracranial hemorrhage) and combined them to develop a model to predict the outcome in patients with moderate to severe TBI who underwent decompressive craniectomy. 2,28,30,31 A study involving pediatric patients (<17 years) reports that children with lower scores have better survival outcome as compared with adults with same scoring, but children with higher Rotterdam CT scores have worst survival as compared with adults. 28 The authors concluded that the Rotterdam CT scoring system can be a relatively objective, simple, and practical tool to prognosticate the outcome in both adults and pediatric patients with TBI.…”
Section: Discussionmentioning
confidence: 99%
“…We recorded the following trauma‐related radiological information: abnormal cisterns, midline shift, skull‐cap fracture, skull‐base fracture, epidural hematoma, subdural hematoma, subarachnoid hemorrhage, intraventricular hemorrhage, cerebral hematoma, brain contusion, and pneumocephalus. Radiological severity was classified in light of the Rotterdam CT classification (Fujimoto, Miura, Otsuka, & Kuratsu, 2016). In addition, progressive hemorrhagic injury, acute lung injury, and post‐traumatic cerebral infarction were defined based on the previous studies (Allard et al, 2009; Bernard et al, 1994; Mirvis, Wolf, Numaguchi, Corradino, & Joslyn, 1990).…”
Section: Methodsmentioning
confidence: 99%
“…Varios estudios han demostrado la utilidad e inclusive la superioridad de esta escala, para la predicción de mortalidad y los malos resultados a corto y mediano plazo de los pacientes con TEC, después de la realización de craniectomía descompresiva e inclusive en pacientes pediátricos 5,6,15 . No obstante en la revisión sobre el tema llevada a cabo por los autores, no se encontró ninguna referencia que abordara la posible utilidad de la misma para realizar el pronóstico de la progresión de las lesiones intracraneales detectadas en la TC inicial, si bien Flint et al (citado por Fujimoto et al) 3 encontraron que la severidad del puntaje de Rotterdam en la TC inicial se asoció al riesgo de expansión de las contusiones encefálicas después de realizar craniectomía descompresiva.…”
Section: Valor Del Puntaje De Rotterdam Para El Pronóstico De Empeoramiento Tomográfico Significativo En Pacientes Con Tecunclassified